2004
DOI: 10.1038/sj.onc.1207655
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide sensitizes prostate carcinoma cell lines to TRAIL-mediated apoptosis via inactivation of NF-κB and inhibition of Bcl-xL expression

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to be selective in the induction of apoptosis in cancer cells with minimal toxicity to normal tissues and this prompted its potential therapeutic application in cancer. However, not all cancers are sensitive to TRAIL-mediated apoptosis and, therefore, TRAIL-resistant cancer cells must be sensitized first to become sensitive to TRAIL. Treatment of prostate cancer (CaP) cell lines (DU145, PC-3, CL-1, and LNCaP) with nitric oxide donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 57 publications
6
108
0
1
Order By: Relevance
“…We have reported that treatment of prostate tumor and non-Hodgkin's B cell lymphoma (B-NHL) cell lines with DETANONOate reduced the NFκB DNA-binding activity attributed to S-nitrosylation of the NFκB p50 subunit by NO. 33,42,43 The above observations suggest that NO is a potent NFκB inhibitor and that DETANONOate mediates its anti-metastatic properties, in part, via suppression of NFκB signaling.…”
Section: Discussionmentioning
confidence: 97%
“…We have reported that treatment of prostate tumor and non-Hodgkin's B cell lymphoma (B-NHL) cell lines with DETANONOate reduced the NFκB DNA-binding activity attributed to S-nitrosylation of the NFκB p50 subunit by NO. 33,42,43 The above observations suggest that NO is a potent NFκB inhibitor and that DETANONOate mediates its anti-metastatic properties, in part, via suppression of NFκB signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Bcl-x L , another NF-nB antiapoptotic target gene, has been shown before to be involved in chemoresistance and TRAIL resistance in an NF-nB -dependent way (82)(83)(84)(85). Inhibition of constitutive NF-nB by overexpression of InB-SR inhibited expression of Bcl-x L (61,83,86,87), and down-regulation of Bcl-x L protein sensitized Panc-1 to TRAIL-mediated apoptosis (88). In addition, we found Bcl-x L to be elevated by TNF-a pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Snitrosoglutathione inhibits the growth of various cancer cells [49] [50]. In addition, organic nitrates [51] diazeniumdiolates [52], syndominides [53], S-nitrosothiols [54] and even metal-NO complexes [55], all display anticancer properties in preclinical models of cancer, mostly cell lines. Since they differ structurally so broadly and their "common denominator" is that they are NO donors, it is fair to conclude that their anticancer properties are due or related to the NO that they release.…”
Section: No As the Mediator Of The Action Of No-nsaidsmentioning
confidence: 99%